RN Perception of a Staff-Driven Professional Development Program - Fardellone, Christine; Meyer, Jennifer; Woolforde, Launette (Advances in Social Sciences Research Journal, 2021)
Nurses who participate in the clinical ladder professional development program have an opportunity to grow at the bedside, gain experience, and improve in the care they provide to their patients. Learning more about the clinical ladder members and how to attract additional members is necessary. The clinical ladder program was developed to promote personal growth and professional development of bedside nurses. Clinical ladder programs have become increasingly well known for the ability to promote job satisfaction, improve employee engagement, and strengthen the quality of nursing care. The theoretical framework of the clinical ladder program is based on Patricia Benner’s Model, “Novice to Expert”. This study will evaluate registered nurses’ perceptions of the effectiveness of the clinical ladder program and the importance of financial compensation. Effectiveness of the program is defined as providing an environment that recognizes clinical excellence and enables nurses to grow in their clinical ability. A convenience sample of 341 staff clinical ladder nurses employed in the Northwell Health System responded to the demographic questionnaire and the Clinical Ladder Assessment Tool survey. The data from the subjective responses were analyzed. Clinical ladder nurses scored 32/36 (89%) responses as positive. Overall, the program was effectively orchestrated. More than 50% of the nurses scored financial compensation as greatest importance. Statistical significance was reported in the perceived effectiveness of the clinical ladder program based on ladder level. The clinical ladder program continues to empower nurses to participate in professional and self-development. The clinical ladder program provides opportunities for collaborating, mentoring, developing new knowledge, engaging in the decision-making process, and acting as advocates and leaders for patient care. Organizations who continue to support professional development of bedside nurses will experience innovations which influence all levels of the health care system.